Application of the Corporate Rescue Concept in Indonesian Bankruptcy Law: Urgency and Reform - Ahmad Akbar, Aliif (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2024)
This study aims to analyze the implementation of the Corporate Rescue Concept within Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (Bankruptcy Law) and to identify its weaknesses, as well as the urgency for legal reform to optimize the business rescue function. The research adopts a normative juridical approach, utilizing doctrinal analysis, comparative law, and a literature review of the Bankruptcy Law’s provisions and its practical implementation. The findings indicate that while the Bankruptcy Law incorporates the Corporate Rescue Concept through the PKPU mechanism and the peace plan, its provisions remain limited and predominantly focus on liquidation. Three critical issues were identified: (1) the lack of detailed provisions on debt restructuring mechanisms, (2) the absence of standards for business feasibility assessments, and (3) insufficient oversight in the implementation of rescue plans. The study concludes by recommending amendments to the Bankruptcy Law to better emphasize the principle of business rescue, including: (1) the regulation of comprehensive restructuring schemes, (2) the establishment of an independent supervisory body, and (3) the provision of incentives for creditors. These reforms are crucial to strike a balance between creditor protection and the continuity of debtor businesses.